Disease-Free Survival in Women with Breast Cancer: 36- and 60-Month Cohorts - Santos, Bruna Mascarenhas (2025)
Introduction: The study of disease-free survival has contributed to understanding the behavior and prognostic factors following the diagnosis of breast cancer in women. Objective: To analyze disease-free survival in 36 e 60 months and prognostic factors in women with breast cancer treated at a private health service. Method: Historical cohort study of women diagnosed with non-metastatic breast cancer seen between 2010 and 2021. Demographic and clinical data were collected. The statistical, descriptive, bivariate, survival analysis usedthe Kaplan-Meier method and the log-rank test. Results: Disease-free survival at 36 months was 89.8% (95%CI: 84.8-93.3) and clinical stage III was the worst prognosis with an 11% reduction in the meantime compared to stage I. Compared to 60 months, disease-free survival was 80.6% (95%CI: 73.1-86.2), with stage II and III having the worst prognosis. The reduction in mean time for stage III was21 per cent compared to stage I. Conclusion: Tumor and clinical characteristics are important for understanding disease-free survival and identifying risk profiles for recurrence, given the scarcity of research on the subject in the Brazilian population. It therefore emphasisesthe need for early diagnosis to reduce recurrence.